Artificial Intelligence Readiness and Digital Transformation in Islamic Secondary Education - Muh. Ibnu Sholeh (CV. Gerasi Insan Nusantara, 2026)
Artificial Intelligence (AI) is increasingly recognized as a catalyst for educational innovation and digital transformation. Despite its growing adoption in educational settings, empirical evidence regarding AI readiness among teachers in Islamic secondary schools remains limited. This study investigates teachers’ readiness, utilization patterns, opportunities, and challenges associated with AI integration at MA Darunnajah Trenggalek, Indonesia. An explanatory sequential mixed-method design was employed, involving 42 teachers in a quantitative survey and 10 teachers in semi-structured interviews. Data were analyzed using descriptive statistics, multiple regression analysis, and thematic analysis. The findings indicate that teachers demonstrate a moderate-to-high level of AI readiness, with technological readiness achieving the highest score (M = 4.11), followed by pedagogical readiness (M = 3.89), ethical readiness (M = 3.74), and institutional readiness (M = 3.56). ChatGPT (92.8%), Canva AI (81.0%), and Gamma AI (66.7%) emerged as the most frequently utilized AI applications for lesson planning, content development, and assessment preparation. Digital literacy (β = 0.52), participation in AI-related training (β = 0.38), and leadership support (β = 0.29) significantly predicted AI readiness, collectively explaining 62.4% of the variance. Teachers perceived AI as a valuable instructional assistant capable of enhancing efficiency, creativity, and student engagement. Challenges were associated with limited professional development opportunities, ethical concerns regarding academic integrity, infrastructure constraints, and the absence of comprehensive institutional policies. Drawing on the Technology Acceptance Model, Artificial Intelligence in Education, and Digital Transformation Theory, this study proposes an AI Readiness Framework for Islamic Schools that integrates digital literacy, ethical awareness, leadership support, professional development, and institutional governance. The findings highlight that sustainable AI integration requires simultaneous investment in teacher competencies, ethical guidance, and organizational transformation to support innovation in Islamic secondary education.